Sexual dimorphism in the cervical vertebrae and its potential for sex estimation of human skeletal remains in a white scottish population - Yuvenya Kaeswaren; Lucina Hackman (Forensic Science International: Reports, 2019)
Background: Biological sex determination from skeletal human remains is crucial in archaeological and forensic settings. The purpose of the current study was to evaluate the presence of sexual dimorphism in seven (C1C7) cervical vertebrae dimensions and to further establish a reliable sex estimation method using C1C7 for a White Scottish population. Method: In this study, three morphometric characteristics from the cervical vertebrae were measured; maximum vertebral body height (CHT), maximum anterior-posterior diameter of vertebral foramen (CAP) and maximum transverse diameter of vertebral foramen (CTR). One-hundred and fifty (150) cervical vertebrae from a total of twenty-five (25) human cadavers (13 males, 12 females) ranging in ages 49 to 103 years were studied. Results: The resulting statistical analysis showed that CHT measurements exhibited the greatest degree of sexual dimorphism at all cervical vertebral level followed by CTR measurements. CAP measurement only exhibited significant sexual dimorphism at the second cervical vertebra (C2AP). A total of 25 multivariate discriminant functions were generated that were statistically significant and successfully assigned sex with an 81.8%–100% accuracy range. A cross-validation study was also performed to establish the reliability of the 25 functions and only eight out of 25 functions exhibited weak statistical reliability. Conclusion: Statistically significant sexual dimorphism in the cervical vertebral dimensions (CHT and CTR) was conclusively established with the second cervical vertebrae (C2) exhibiting the greatest sexual variance in the cervical vertebral column of a White Scottish population. Age-related changes were not observed in the vertebral dimensions of the study sample and this may however be due to the insufficient sample size for each age category. Keywords: Forensic anthropology, Forensic anthropology population data, Forensic science, Sex estimation, Discriminant function, Cervical vertebra